Outcome of Single Layer Extra Mucosal Interrupted Suture in Intestinal Anastomosis - A Prospective Study of 50 Cases in a Tertiary Level Hospital - Mahmod, Mohammed Sultan (The Insight, 2023)
Background: Anastomosis is required to be done in different operations where part of the gastro intestinal tract is resected for benign or malignant causes. Leakage from the anastomosis site is a major complication that is often associated with increased morbidity and mortality and prolonged hospital stay. Apart from other factors, appropriate suturing technique is still a mainstay in the safety of anastomosis. Many surgeons continue to practice double layer intestinal anastomosis which incorporates inner layer of continuous through and through and outer layer of sero-muscular interrupted suturing while some surgeons confidently use single layer extramucosal interrupted suture. Aim: This study was conducted with an intention to observe the outcome of single layer extramucosal interrupted suture in intestinal anastomosis in the patients and to draw a comparison between the two techniques. Materials and methods: This Case control study was conducted in the general surgery wards of Sher-E-Bangla Medical College Hospital, Barisal for a period of twelve months from July 2012 to June 2013.Fifty patients who underwent surgery for intestinal anastomosis during the study period were included in this study by consecutive sampling. At enrollment particulars of patient and particulars of the operation were recorded. Preoperative investigations, patient preparation, perioperative I/V fluids and analgesics were given according to the standardized protocol. The patients were divided into two groups. In group-l single layer extramucosalsero-muscular and in group-ll double layer anastomosis were constructed, each applied to the alternate patients. Result: Fifty patients were included in this study. Twenty eight (56%) patients were males and Twenty two (44%) patients were females. Male to Female ratio was 1.70: 1. Age ranged from 15 years to 60 years. Return of bowel function was quicker in single layer extramucosal interrupted sutureinintestina anastomosis group than double layer group- average 72.72±19.77 hours and 82.48±18.70 hours respectively. Postoperative first oral intake was 86.92+13.73 hours in single layer group and 95.36±12.75 hours in double layer group. Wound infection developed in two (8%) patients in group-l and three patients (12%) in group-II. Anastomotic leakage occurred in total three patients- one patient (4%) in group-l while two patients (8%) in group-II. One patient in group-ll (double layer) died of sepsis and multi organ failure. Mortality in group-I was 0% while in group-llit layer group- 9.84±2.84 days in group-I and 11.48±3.53 days in group-II. Conclusion: Single-layer extra mucosal interrupted intestinal anastomosis can be done without complications. To reduce post-operative complications, intestinal anastomosis surgery should be performed after nutritional buildup, anemia correction, electrolyte imbalance correction, stoma duration, and a technically qualified and experienced surgeon. It's safe for surgical training.